Залучення технологій ГІС до проведення післяпроєктного моніторингу діяльності автозаправних станцій - Козуля, Тетяна Володимирівна; Коршунов, Святослав Євгенійович (Інститут агроекології і природокористування НААН, 2025)
The study discusses the principles of filling station planned activities from the point of view of comprehensive consideration of environmental and social hazard factors for further developmening the concept of technogenic activities comprehensive monitoring for the excessive environmental impact’s early prevention and prevention of emergency situations, or damage reduction from possible consequences. Proposed ways to increase monitoring efficiency through the introduction of GIS technologies.
Involvement of GIS technologies in post-project monitoring of gas station activities
Keywords: географічна інформаційна система; оцінка впливу на навколишнє середовище; післяпроектний моніторинг; автозаправна станція; інтегроване програмне забезпечення контролю навколишнього середовища; geographic information system; environmental impact assessment; post-project monitoring; gas station; integrated environmental control software